Biological Activities of Snowdrop (Galanthus spp., Family Amaryllidaceae) - Kong, Chee Kei; Low, Liang Ee; Siew, Wei Sheng; Yap, Wei-Hsum; Khaw, Kooi-Yeong; Ming, Long Chiau; Mocan, Andrei; Goh, Bey-Hing; Goh, Poh Hui (Frontiers in Pharmacology, 2021)
Snowdrop is an iconic early spring flowering plant of the genus Galanthus (Amaryllidaceae). Galanthus species (Galanthus spp.) are economically important plants as ornaments. Galanthus spp has gained significance scientific and commercial interest due to the discovery of Galanthamine as symptomatic treatment drug for Alzhiermer disease. This review aims to discuss the bioactivities of Galanthus spp including anticholinesterase, antimicrobial, antioxidant and anticancer potential of the extracts and chemical constituents of Galanthus spp. This review highlights that Galanthus spp. as the exciting sources for drug discovery and nutraceutical development.